OPTIMASI STRUKTUR UNTUK MENDAPATKAN FREKUENSI ALAMI YANG TERPISAHKAN SECARA OPTIMAL - Satryo Soemantri B; I Wayan Suweca; Endra Sujatmika (Mesin, 1998)
In obtaining the dynamic response of a dynamic system, its uncouple modal equation of movement simplifies the usage of superposition modal method. This paper proposes a strategy to obtain the uncouple modal equation based an hypotheses of Basile : "Although the presence of modal-damping-couple, the modal equations of movement are dynamically uncoupled for a structure having small damping coefficient if its natural frequencies are well-separated"(1). This hypotheses is justified by several authors, i. e. by Hasselman(1). Thus, by separating the natural frequencyof a dynamic system using Hasselman criteria, it is expected that the modal equation of movement will become uncoupled. The separation of the natural ï¬equency is done by optimization method which is conducted by using the ï¬nite element software ANSYS.